(3eMGSHI GdfaSs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3CMeO Hf eMeO Hf CMeO GdedbH HQVi s)
(3ChdgG (B:s
(3Yf TOGO Hf ChS QVi Gddg Yfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3GdcjS ef OGf faSg hYed deG HYO GdehJ hGdYGLR ef CJHY faSg ghGgG hJefi Ydi Gddg (B) s
(3BNQgG (B:s
(3hcGf jbhd dfaSg eGdc ef GdWYGe eG faS EdG GdNHR hGdRjJ heGdc ef GdKjGH Edi gPG GdKhHGf heGdc ef GdfSGA EdG gPg GdYLhR abGdJ Cf CUHQ Ydi gPG GdYjT Je cJGH eMGSHI GdfaS dGHf CHj GdOfjG GdbQTi s
(3GdhQb dhfg bGJes
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1608s
Keywords: (3GdJUha hGdBOGH GdTQYjIs